Plastid Phylogenomic Data Offers Novel Insights Into the Taxonomic Status of the Trichosanthes kirilowii Complex (Cucurbitaceae) in South Korea - Park, Inkyu; Song, Jun-Ho; Yang, Sungyu; Chae, Sungwook; Moon, Byeong Cheol (Frontiers in Plant Science, 2021)
Trichosanthes is a genus in Cucurbitaceae with 90–100 species. Trichosanthes species are valuable as herbaceous medicinal ingredients, and the fruit, seeds, and roots of species such as T. kirilowii and T. rosthornii are used in Korean traditional herbal medicines. However, T. rosthornii is only found in China, and Korea only has one reported Trichosanthes species and one variant of that species, T. kirilowii and T. kirilowii var. japonica. T. kirilowii and T. kirilowii var. japonica have different inflorescences and leaf shapes but are recognized as the same at the species level. Species classification for Trichosanthes is complex, and although its members have value in herbal medicine, there are still limited genomic resources on this genus. In this study, T. kirilowii and T. kirilowii var. japonica were reclassified by sequencing chloroplast (cp) genomes from five Trichosanthes accessions, with the broader goal of preventing herbal medicinal plants from being confused and adulterated. The cp genomes were 156,790–157,155 bp long and exhibited a conserved quadripartite structure. 113 genes were identified in total, including 79 protein-coding regions, 30 transfer RNA (tRNA) genes, and four ribosomal RNA (rRNA) genes. The gene order, content, and orientation of the five Trichosanthes cp genomes were highly conserved and were consistent with the general structure of angiosperm cp genomes. Comparison of the five Trichosanthes cp genomes revealed locally divergent regions, mainly within intergenic spacer regions (trnT–UGU- trnL–UAA, rrn4.5–rrn5, trnE–UUC–trnT–GGU). In addition, indel marker sets (Tri, TRr, and TRtt) were developed to identify the important herbal medicine species in Trichosanthes. Novel markers were applied for commercial products in Korea. We uncovered high-resolution phylogenetic relationships among Trichosanthes species. Phylogenetic analysis of the five Trichosanthes species revealed that these species well clustered as Tribe Sicyoeae. T. kirilowii and T. rosthornii had monophyletically with T. kirilowii var. japonica as a sister, and we therefore suggest that T. kirilowii and T. kirilowii var. japonica be reclassified into different species. Our study uncovers two types of T. kirilowii in Korea, establishes relationships in Cucurbitaceae, provides a useful evolutionary analysis of the Trichosanthes genome, and gives novel markers that can be used to authenticate herbal medicines.